Two-Dimensional Layered Amorphous Metal Oxide Gas Sensors (LAMOS) Perspectives and Gas Sensing Properties - Valentina Paolucci; Jessica De Santis; Vittorio Ricci; Giacomo Giorgi; Carlo Cantalini (Proceedings)
Two-dimensional Layered Amorphous Metal Oxide Sensors (LAMOS) represent a new class of 2D amorphous oxide (a-MOx) interfaces with unveiled properties in gas sensing applications. Herein, we report the humidity and gas sensing response of p- and n-type chemoresistive few-layered (2D) amorphous a-SnO2, a-In2O3, and a-Cr2O3, discussing their reaction mechanisms using DFT modelling and electrical tests. LAMOS interfaces can be easily prepared by controlled oxidation in air of a large class of exfoliated 2D TMDs, MCs, and TMTH (Transition Metal Dichalcogenides, Chalcogenides, and Trihalides) like WS2, MoS2, SnSe2, In2Se3, NiCl2, and CrCl3, yielding 2D amorphous a-MOx interfaces. LAMOS platforms preserving all the surface-to-volume advantages of their 2D precursors show excellent gas sensing properties representing a new class of material for gas sensing applications.